Pelaksanaan Perjanjian Pembiayaan Murabahah Dengan Sistem Bai’u Salam (Studi Pada PT. BPRS Daya Artha Mentari Bangil-Pasuruan) - Dyah Ochtorina Susanti (Jurnal Risalah Hukum, 2010)
Murabahah Financing Contract with Bai’u Salam system, is a combination between Murabahah financing and Bai’u Salam financing, that is an innovation in improving Syari’ah banking products. In practice, the financing system implemented Islamic Muamallah principles, and the standardized contract implemented contract principles complied with Islamic laws and Civil Laws enforced in Indonesia. Based on them, the implementation of the combination of the two financings has complied with Islamic Laws (Muamallah principles and Islamic contract principles) and contract law principles in Civil Laws enforced in Indonesia.